SOSIALISASI PEMANFAATAN ENERGI TERBARUKAN KEPADA KELOMPOK NELAYAN DI DUSUN CEMARE - Ida Bagus Fery Citarsa; I Ketut Wiryajati; I Nyoman Wahyu Satiawan; I Made Budi Suksmadana; Supriono; Cipta Ramadhani (Jurnal Bakti Nusa, 2026)
Fishermen, as a part of the human resources that require energy in carrying out their activities, need to prepare themselves with knowledge about the use of renewable energy for future needs. The 'Obor Kehidupan' Fishermen's Group in Cemare Hamlet does not yet have knowledge about renewable energy due to their lack of educational background. This activity has a purpose about renewable energy socialisation so that the fishermen's group member able to understand the various types of renewable energy and the potential of renewable energy in their area. Based on interviews before the socialisation, it was found that the knowledge of renewable energy among the fishermen's group members was still lacking. After the socialisation was conducted, the results were obtained that 73.91% of participants answered questions about renewable energy with a score of sufficient to very good, while 26.09% of participants answered the same question with a score of very poor to poor. This indicates that the socialisation that have been carried out have provide an understanding of renewable energy to the majority of the fishermen's group members.